PELATIHAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA BAGI PETERNAK DOMBA DI WILAYAH BUGEN KELURAHAN TLOGOSARI SEMARANG - Setyowati, Ani; Pardiyanto, Martinus Aditya; Kartika, Shinta Eka; Manan, Abdul (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Financial statements is a part of an entity’s responsibility in informing the condition of assets, liabilities and equity. With financial reports, an entity’s financial condition can be traced and its effectiveness in managing finances assessed. Apart from that, financial reports can be used as a tool to take measurements to ensure business capabilities in carrying out operations. Besides that financial statements projections of future business operations can be planned better. Livestock farming is an important sector in the process of meeting society’s needs, but not all livestock business managers understand the importance of bookkeeping reports. Therefore, training and assistance in making simple financial reports is needed to help livestock farmers in managing their livestock businesses. The location for mentoring and training is in the Bugen area, Tlogosari Wetan Village